Chamomile industrial profiles - Franke, Rolf (Taylor & Francis, 2005)
For over 2000 years, preparations of chamomile flowers have counted among the medicinal treasures of many cultural groups. This book provides an interdisciplinary inventory of the scientific level of knowledge about German chamomile as well as Roman chamomile, the two types of chamomile most produced. It includes information for pharmacists and the pharmaceutical industry about chamomile preparations and essential chamomile oil. Physicians and toxicologists will find detailed descriptions of the latest experimental studies and the use of chamomile preparations in traditional and therapeutic uses. It also includes the latest information of use to growers and pharmaceutical entrepreneurs.